Chemical composition and amino acid profile of differently processed feather meal - Adejumo, Isaac Oluseun; Adetunji, Charles Oluwaseun; Ogundipe, Kunle; Osademe, Sonia Ndudi (Journal of Agricultural Sciences (Belgrade), 2016)
Feather wastes represent potential alternative ingredients for animal feedstuffs which can ameliorate the protein shortage for food and feed. Previous attempts to provide information about the nutrient composition of feather meal is either too complicated for rural livestock farmers in developing countries or they provided incomplete information on chemical composition. Washed feathers were subjected to different processing techniques such as pre-soaking in distilled water, wood ash, 0.3M NaOH, a mixture of wood ash and 0.3M NaOH, incubated at 37oC and boiled at 150oC for 60 minutes. Treated feather meals were analysed for chemical composition and amino acid profile. The overall result showed that feather meal pre-soaked with wood ash for 24 hr boiled at 150oC for 60 minutes, those pre-soaked with 0.3M NaOH and wood ash incubated at 37oC for 24 hr boiled at 150oC for 60 minutes and raw feather meal pre-soaked in distilled water for 24 hr boiled at 150oC for 60 minutes gave a better results. Wood ash and 0.3M NaOH and their mixture could enhance the nutritional value of feather meal.